2021
DOI: 10.2320/matertrans.c-m2021835
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Corrosion Resistance of Ta-Bearing Duplex Stainless Steel

Abstract: The effect of Ta addition on the pitting corrosion resistance of duplex stainless steels was investigated in both cases without and with deoxidization/desulfurization by the addition of Al and Ca. The pitting corrosion resistance was improved by the addition of Ta with two proposed mechanisms. For steels without Al and Ca, the MnS inclusions which act as initiation sites of the pitting corrosion are modified to the electrochemically-stable (Ta,Mn) oxysulfides. For steels with Al and Ca, the pitting initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has been reported that tantalum additions can hinder the precipitation of harmful phases, which improves the pitting corrosion resistance [67,68] . Further studies showed that tantalum forms nitrides that coat the CaS and (Al, Ca) oxides.…”
Section: Titanium Niobium and Tantalummentioning
confidence: 99%
“…It has been reported that tantalum additions can hinder the precipitation of harmful phases, which improves the pitting corrosion resistance [67,68] . Further studies showed that tantalum forms nitrides that coat the CaS and (Al, Ca) oxides.…”
Section: Titanium Niobium and Tantalummentioning
confidence: 99%